PENGARUH KETEBALAN BAHAN ALUMINIUM TERHADAP INDUKSI MAGNETIK YANG DITIMBULKAN OLEH TELEPON SELULER - Lendra Kusma; Erwin '; Salomo ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Nowadays, a cellular phone is an important communication tool therefore, biologically the electromagnetic radiation produced from the cellular phone on the users become relevant. The measurement of magnetic induction generated by three brands namely A, B and C of cellular phone was carried out. The measurement was done for two directions such as horizontal and vertical direction. In order to investigate the effect of alumunium thickness on magnetic induction, several slabs of alumunium with the thichness of 1 mm – 4 mm were prepared. An instrument used for measuring the magnetic induction was magnetic sensors Pasco 2162. The magnetic induction was measured in horizontal direction at a distance of 0,5 cm from cellular phone with and without using an aluminium slab. The results showed that the magnetic induction in horizontal direction generated by cellular phone brand A is highest among A, B and C with the value of 1,09x10-4 Tesla, 1,07x10-4 Tesla, 9,75x10-5 Tesla respectively. The value of magnetic induction generated by a cellular phone reduces when a slab of alumunium was inserted between cellular phone and sensor. The measurement of the magnetic induction in a vertical direction shows that the further distance of the sensor to the cellular phones and the smaller the magnetic induction observed. The result also showed that the value of magnetic dipole moment of cellular phone based on the plot of magnetic induction versus distance is 1 Am2.